Tingkat Kecerdasan Moral Pada Pembelajaran Kewarganegaraan - Isnaini Septa Azzahra (JURNAL PENCAKAR (Pendidikan Pancasila dan Kewarganegaraan), 2026)
An Civic education is one of the main topics school, the aim of which there are to promote civic intelligence spiritual, rational, emotional and social aspects, foster a sense of social responsibility, and train students to participate as citizens and become good citizens. Only in this way can the outlook on life work well and lead the country to become a developed country. Morality is good behavior that becomes the character of an individual or group and is reflected from within the way of thinking, acting and reacting to situations. In this case, Pancasila is the morality Indonesian people, which is the foundation of the state and its behavior, as well as a reference for adopting attitudes and policies. The morality of the nation affects the organization of the life of the people and the country, applying it establish laws and procedures so that the results obtained in the form of politics become the values ​​produced by the morality of the nation. the nation nationality With Pancasila morality in Indonesia, Pancasila values ​​become behaviors that can be seen and implemented In the life of the Indonesian people and country.